THE IMPACT OF DEMONSTRATION METHODS SUPPORTED BY ABACUS MEDIA ON THE ADDITION SKILLS OF INTEGERS 1-10 IN CHILDREN WITH INTELLECTUAL DISABILITIES - Jilan Huwaida Ahid (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2024)
This research aims to apply a demonstration method using an abacus which can overcome the problem of counting 1-10 in mentally retarded children. This research uses a type of experimental research, namely single subject research with a B-A-A-B design. The data obtained was analyzed using quantitative descriptive analysis and then clarified using graphs and tables. The subjects of this research were students with moderate mental retardation who experienced difficulty in solving addition calculation problems. From the research results, the intervention phase-1, baseline-1, and intervention-2 experienced an increase after being given the intervention and in the baseline phase-2 there was a decrease because the intervention was not provided for a long period of time. With the demonstration method assisted by abacus media, there is an influence on the numeracy skills of mentally retarded students.